Development of Artificial Hand Gripper by using Microcontroller - Mohd Ali, A. M.; M. Wahi, A. J.; Ambar, R.; Abdul Jamil, M. M. (International Journal of Integrated Engineering, 2011)
This paper focuses on the development of a measurement hand gripper to help handicap patient due to accident and diseases. Basically, when the patient needed to perform exercises they must get an appointment with a doctor. Normally this will take few weeks or months. This is because the rehabilitation devices at Physiotherapy Department in hospital are very limited. From this problem, we suggest to develop a reasonably cheap home-based rehabilitation measurement devices which can perform the task of assisting paralyze patient at home. The basic movement of the patient was limited from a wrist, elbow and shoulder. The development of this project involves the designing of a sensors equipped Smart Glove and a measurement hand gripper device. The hand gripper device will move based on a human operator’s finger movement using the Smart Glove. The purpose of our project is to design and develop a master-slave system robotic hand which can be a substitution for the paralyzed hand in therapy to aid in recovery process of patients upper limb function. The project involves an Arduino microcontroller for the instrumentation, communication and controlling applications. A series of flex sensors are fitted in a master glove to get readings from the movement of human fingers. Microcontroller will further use this information to control multiple servos that controls the movement of slave robotic hand.